Identifying and assessing Spice and herbs resources for tourism attractions: A case study from Banyuwangi, East Java - Luchman Hakim; Soemarno Soemarno; Bagyo Yanuwiyadi (Research Journal of Life Science, 2016)
The aims of the study was to analyze the potentiality of spices and herbs in agrofotestry garden in Banyuwangi, Indonesia, for further rural tourism development. Fields study was set up at villages in Banyuwangi. Floristic survey, ethnobitanical studies and focus group discussion were performed to evaluate the value of spices and herbs in agroforestry gardens an its potentiality to develop as tourism product. This study found that at least 60 species of spice and herbs with its special value, in which these species has opportunities to developed as tourism attraction in agroforestry garden. There are something to see, something to buy and something to do has been described by group discussion participant. It is raging from farm tourism product, culinary tourism product and heath-wellness tourism product.